Construction of Tb3+ PVC-MembraneElectrode Based on N,N’-Bis(pyrrolylmethylene)-2-aminobenzylamine - Hassan Ali Zamani; Zynab Rafati; Soraia Meghdadi (E-Journal of Chemistry)
In this work, we report as new Tb3+-PVC membrane sensor based on N,N’-bis(pyrrolylmethylene)- 2-aminobenzylamine (PMA) as a suitable ion carrier. Poly vinylchloride (PVC)-based membrane composed of PMA with oleic acid (OA) as anionic additives and acetophenone (AP) as plasticizing solvent mediators. The Tb3+ sensor exhibits a Nernstian slope of 19.7±0.4 mV per decade over the concentration range of 1.0×10-5 to 1.0×10-2 M and a detection limit of 4.6×10-6 M of Tb3+ ions. The potentiometric response of the sensor is independent of the solution pH in the range of 2.9–8.1. It has a very short response time, in the whole concentration range (∼5 s). The recommended sensor revealed comparatively good selectivity with respect to most alkali, alkaline earth, some transition and heavy metal ions. It was successfully employed as an indicator electrode in the potentiometric titration of Tb(III) ions with EDTA. The electrode was also employed for the determination of the fluoride ion in two mouth wash preparations and the determination of Tb3+ ions concentration in mixtures of three different ions.